STUDENTS’ VOCABULARY MASTERY AND THEIR READING COMPREHENSION - Lestiana, Siti; Ilma, Ridha; Saputra, Eko (English Community Journal, 2025)
Vocabulary mastery is one of the important components of language to learn. This study investigated the correlation between vocabulary mastery and reading comprehension and the influence of vocabulary mastery and reading comprehension. A total of the sample in this study was 105 students from eighth grade students. Vocabulary mastery test and reading comprehension test were the instruments to collect the data. The descriptive statistics and Pearson Product Moment correlation coefficient were used to analyze the data in this study. The findings of this study showed that there was a significant correlation (r = 0.243) was higher than r-table (.190). Then, the level of probability (p) significance (sig.2-tailed) was 0.013 was lower than 0.05. Thus, there was a significant correlation between the students’ vocabulary mastery and their reading comprehension. From the results of regression analysis with a degree of significance of 0.013 showed that there was an influence of the vocabulary mastery on the reading comprehension of 5.9%.it could be concluded that mastery of student vocabulary was an important factor in achieving student reading comprehension.